UPAYA DETEKSI DAN PENCEGAHAN PERUNDUNGAN (BULLYING) DI SMPN SATU ATAP DESA SUKA MAJU KEC. MESTONG KAB. MUARO JAMBI - Mila Triana Sari; Daryanto Daryanto (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2019)
Cases of bullying or violence against children in Indonesian schools currently rank second largest after Japan. While the United States itself is under Indonesia. (Indra, 2016). As many as 84 percent of children aged 12 years to 17 years have been victims of bullying (Viva, 2017). The impact on children who experience Bully will cause adverse effects such as reluctance to go to school, decreased learning achievement, tension, bruises or injuries on the body and ask to change schools and so on. One of the efforts that nurses can do is provide health education to students and teachers. One Roof Junior Secondary School is a partner school, which cares about bullying, but has never carried out health education activities on prevention of Bulllying. The target and outcome of this activity to community service is to provide an understanding of the concept of bullying so that it can detect and make prevention efforts both as perpetrators and victims. The implementation method used is survey, observation, interview, discussion, question and answer through giving information about Bullying detection and prevention at the One Roof Junior High School of Suka Maju Village. The target of the Activity is all students and Teachers of One Roof Junior High School in Suka Maju Village, Kec. Mestong Kab. Muaro Jambi. The service activities are carried out starting from preparation, implementation and evaluation within April 24 to May 12, 2018. Before and after health education students are given questions about Bullying, detection and prevention. Students' knowledge about detection and prevention of bullying was measured before and 1 week after counseling. Results of the activity A total of 45 students and 4 teachers participated in the implementation. Most participants considered that health education activities were beneficial for them in early detection and actively made efforts to prevent bullying both as victims and perpetrators among students and teachers.